Pengaruh Kerja Paruh Waktu Terhadap Prestasi Akademik Mahasiswa UIN SU - Mukhammad As Alukal Huda; Mei Fani; Ramadian Magvira Saragih; Dini Lestari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The influence of part-time work on the academic achievement of students at the State Islamic University of North Sumatra (UINSU). Working part-time while pursuing higher education is one of the activities frequently undertaken by students to earn additional income. Additionally, part-time work can also provide valuable experience and skills for students in the future. However, on the other hand, engaging in part-time work can also impact students' academic performance. This research aims to comprehensively and deeply understand the effects of combining work and study activities on the academic achievement of UIN North Sumatra students who work part-time off-campus, taking into account the existing issues. To achieve this goal, a quantitative research approach was employed. Based on the results of a questionnaire given to respondents regarding the influence of part-time work on the academic achievement of UIN North Sumatra students, using 15 statements, the percentage of responses was as follows: respondents strongly agreed at 8.01%, agreed at 27.09%, neutral at 43.49%, disagreed at 16.02%, and strongly disagreed at 5.38%. The total score obtained was 5172, with an average of 3.16. There appears to be a significant impact between part-time work and the academic achievement of UIN North Sumatra students, but with a negative direction. This means that the less time spent on studying, the lower the academic performance achieved. This is caused by the difficulty faced by UIN North Sumatra students who study while working in managing their time.